O operador do Direito da Defensoria Pública do Estado de São Paulo no atendimento à violência contra a mulher - Bernardes, Isabel Cristina Gonçalves (2016)
To investigate the care provided by Defenders of the Public Defender of the State of São Paulo to the question of violence against women appearing in the screening of the institution. Rationale: Surpass the logic behind the practices of violence against women, domestically and in the public and institutional scopes is one of the biggest challenges of Brazil, according CPMI Final Report on violence against women, delivered in August 2013 for Senate and Congress. The Public Defender is a fundamental key to this challenge be won, to understand modes, strategies and difficulties of professionals that participate in the initial reception of the legal requirements with respect to this issue is the first step to achieve the eradication this type of violence. Theoretical and methodological aspects: To support this work, we use the discussion of Guacira Lopes Louro about gender stereotypes and Agnes Heller about the naturalization of experienced situations daily and linking them to the current literature on the issues of violence against women and the understanding of professionals that receive women victims of violence. Were done 18 interviews with six women professionals and five men professionals in leadership positions in the researched institution, four men professional and three women professional that work in screening. Results: Identification and referral of demands involving violence against women are big difficulties for professionals of the institution, especially when such violence underlies other legal demands. This difficulty is also due to the organization of this Public Defense and adds to organization and care provided by other institutions and services to this question. Surpass the banality of this type of violence that is manifested, is a possible path to your inquiry pass to a job step and the care of this population be refined. Training on the subject is the most cited by interviewers (women and men) to reach these goals